NILAI TAMBAH PENGOLAHAN BUAH STROBERI MENJADI JUICE DOUBLE BERRY (STUDI KASUS COFFE D’MOOAT DI DESA MOOAT KABUPATEN BOLAANG MONGONDOW TIMUR) - Dormina Mike Sombuk; Agnes Estephina Loho; Rine ., Kaunang (AGRI-SOSIOEKONOMI, 2019)
This study aims to analyze the added value of strawberry processing into double berry juice at Caffe D’Mooat in Mooat Village, East Bolaang Mongondow Regency. The research location was chosen deliberately, namely the area that cultivated strawberries in Bolaang Mongondow Timur District, Mooat Village. This research was conducted from August to October 2018. The Caffe D’Mooat research site was in Mooat Village, Bolaang Mongondow Timur Regency. The data used are primary data and secondary data. Primary data is data obtained from observations and direct interviews with the owner of Caffe D’Mooat (one respondent) based on the questionnaire (questionnaire) that had been prepared previously. Secondary data was obtained from Caffe D’Mooat's profile, local bookstore, internet through google scholar to get electronic books, journal articles and thesis related to the topic of research on the added value of strawberry fruit. The method used in this study is a case study method. Data obtained were analyzed using value added according to the method of Hayami et al. (1987). The results of this study indicate that in one process the production of double berry juice provides added value of Rp. 68.54/gram.*eprm